Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 756745 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Amphipoda" ] } The dataset includes 756745 records from 1038 constituent datasets: 463 records from Natural history museum data on Canadian Arctic marine benthos. 1 records from arim. 42 records from Gloucestershire Historic Wildlife Sightings prior to 1st Jan 2000. 29 records from BenthosChukchiFN762_1976_Falk5. 1 records from Exploring Fronts With Multiple Robots – Schmidt Ocean Institute Cruise to the Pacific Ocean in 2018. 3 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 27 records from North Sea plastic incubation and reference communities, raw sequence reads. 4 records from Marine metagenome ICM_JRV. 71 records from Macrozoobenthos composition, abundance and biomass in the Arctic Ocean along a transect between Svalbard and the Makarov Basin 1991. 4 records from A new species of Ceradocus Costa, 1853 (Senticaudata: Maeridae) from Ceará State, Northeastern Brazil. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 2 records from Anophtalmic and epigean? Description of an intriguing new species of Hyalella (Amphipoda, Hyalellidae) from Brazil. 2 records from A new species of Deutella Mayer 1890 (Crustacea: Amphipoda) from the Mexican Pacific coast. 1 records from Grundschule Sandheide. 1360 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 25736 records from Environment Agency England and Wales (2012) Non-native Species records v1. 35 records from Nekton and plankton counts from Wechselnetz-Hai (300 µm) hauls of cruise GAE 1975/76. 39 records from Seasonal dynamics of sub-ice fauna below pack ice in the Arctic (Fram Strait). 7 records from Paleobiology Database. 7 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 11 records from Species of the Maera - clade collected from Japan. Part 2: genera Austromaera Lowry & Springthorpe, 2005 and Quadrimaera Krapp-Schickel & Ruffo, 2000 (Crustacea: Amphipoda: Maeridae). 77 records from Zooplankton communities in the coastal water of northeastern Hokkaido. 4 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 6 records from (Table 2) Megafauna density 2002, 2004 and 2007 in the deep-sea observatory AWI-HAUSGARTEN, Fram Strait. 9 records from New Zealand fish and squid distributions from research bottom trawls 1964-2008. 2 records from Römertal (Steinpleis). 20 records from HBRG Other Invertebrates Dataset. 574 records from Macrobenthos monitoring in function of dredge disposal monitoring in the Belgian part of the North Sea. 43 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 5036 records from flora&fauna(NIBR)2019. 625 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 46 records from Antarctic Isopods. 3775 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 21 records from On the genus Elasmopus Costa, 1853 from the Northeastern Coast of Brazil with five new species and new records. 7 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 440 records from naturgucker. 32 records from (Table 3a and b) Median biomass of macrobenthos in surface sediments. 4 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 3 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 4 records from Benthic macrofauna abundance of subcores of sediment core 13200-045. 13 records from University of California Santa Barbara Invertebrate Zoology Collection. 447 records from iNaturalist Research-grade Observations. 304 records from Zoobenthos data from the Southern Beaufort Sea, 1971-1975. 1 records from Programme Ecoscope: données d'observations des écosystèmes marins exploités (Réunion). 4 records from IG TUT paleontology. 16393 records from Canadian Museum of Nature Crustacea Collection. 2757 records from The crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 955 records from Crustacea collection of the Finnish Museum of Natural History. 1 records from Hintere Halde. 27 records from Crustacea specimens of Toyama Science Museum. 384 records from New genera, species and records of Maeridae from Australian Waters: Austromaera, Ceradocus, Glossomaera, Hamimaera, Huonella gen. nov., Linguimaera and Maeraceterus gen. nov. (Crustacea: Amphipoda). 1 records from Mittelriede Höhe Gliesmarode-Braunschweig. 48 records from Seawater carbonate chemistry and benthic marine community during experiments, 2011. 5 records from Atlas of Life in the Coastal Wilderness - Sightings. 3 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/367-1. 253 records from Verified Marine records from Indicia-based surveys. 5 records from Abundance of benthos infauna at station PS1240-1. 2 records from BioGIS - Marine snails - HUJ collections. 12 records from Canadian Museum of Nature Parasite Collection. 20107 records from Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 1019 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 35 records from Comparative study of the organismic assemblages associated with the demosponge Sarcotragus foetidus Schmidt, 1862 in the coasts of Cyprus and Greece. 66 records from bioman_belgium. 23 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1 records from marine sediment Raw sequence reads. 12 records from Chucki_Seaooplankton1953/4. 31 records from Amplicon sequencing of Tara Oceans RNA samples corresponding to size fractions for protists.. 3 records from Macrofauna, entomofauna y vegetación vascular de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 12 records from Meiobenthos of target sites of Crimea in 2009/2010. 3 records from Données entomologiques sur la Réserve Naturelle de l’Étang Noir. (Seignosse, Landes). Bilan des études 2001 à 2009. 364 records from Weddell Sea macrozoobenthos EASIZ I. 6 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 3 records from Seawater metagenome Targeted loci environmental. 17 records from Temporal evolution of zooplankton by WP2 net in the Northwestern Mediterranean Sea, Villefranche-sur-mer 2004-2010.. 1 records from Art´n Vielfalt im Kinderwald. 1 records from Klosterwald Itzehoe. 19925 records from Naturalis Biodiversity Center (NL) - Crustacea. 3 records from SNH Invertebrate Site Condition Monitoring of Invertebrate Assemblages at ten SSSIs, 2011-12. 1 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 3555 records from flora & fauna(NIBR). 17 records from Kongsfjorden/Spitsbergen - soft bottom fauna. 3 records from Benthic macrofauna abundance of sediment core 13201-002. 347 records from Macroinvertebrate abundance in river biotopes across England and Wales. 84 records from FBIP:IZIKO-UCT:Historical Survey (1930-1980). 36 records from Red Sea Zooplankton Raw sequence reads. 158 records from Zooplankton Eastern Arctic Ocean Polarstern, 1995-1998. 1 records from Sahrbachtal Kreis Ahrweiler. 1 records from Lüner Holz (Lüneburg). 1365 records from Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by English Nature. 9 records from seawater metagenome Metagenome. 3 records from Plankton sample collected from Nanaimo Harbour Targeted Locus (Loci). 1 records from Meiobenthos investigations in the Black Sea during Poseidon cruise POS317/3. 348 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 4 records from Meiofauna abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 21 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 58 records from Thaumatelsonine Stenothoids (Crustacea, Amphipoda). Part 2. 2 records from Weidenhüttendorf an der Würm (München). 3 records from University of California Museum of Paleontology. 18 records from Ibaraki Nature Museum, Arthropoda collection. 8 records from Colección Limnológica Universidad de Antioquia. 296 records from Zooplankton abundance in the Kerguelen Axis region 2016. 17 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 2 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 2 records from Sea ice and seawater Raw sequence reads. 19 records from Invertebrate data from Selected Grazing Marshes. 3 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 1 records from Données naturalistes de François BRETON. 15 records from FBIP:SAEON: Historical Research Survey Database (1897-1949). 4 records from Naturalis Biodiversity Center (NL) - Mollusca. 1 records from Gieselbachtal Fulda-Harmerz. 113 records from Crustacea specimens of Ryukyu University Museum (Fujukan). 13 records from Siphonoecetini Just, 1983 (Crustacea, Amphipoda, Ischyroceridae) 11: Cephaloecetes schioettei sp. nov. from The Philippines. 2 records from Metazoan sequencing. 3 records from CM Vertebrate Paleontology Collection. 25 records from Abundance of macrozoobenthos in surface sediments sampled during POLARSTERN cruise ANT-V/1. 8 records from Ensigeropus, a new genus of the family Platyischnopidae (Amphipoda: Amphilochidea) from Northern Chile. 3228 records from SIRFF - FNE Centre-Val de Loire - Données 2016. 28 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG95A. 277 records from Nekton and plankton counts from neuston net (300 µm) hauls of cruise GAE 1975/76. 63 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 485 records from Non Native Species Across Wales (1989 to 2012). 348 records from Abundance of benthic infauna in surface sediments from the North Sea sampled with TYRO in 1986. 2 records from Glemstal (Leonberg). 960 records from Invertebrates Collection of the Swedish Museum of Natural History. 315 records from Auckland Museum NZ Marine Collection. 2 records from Gronau - auf der Suche nach dem Neunauge. 8 records from The Sea Ice Fauna of Frobisher Bay, Arctic Canada 1981 and 1982. 1934 records from Biological observations from the Discovery Investigations 1925-1952. 5 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 3 records from Microbial diversity and skin mucosal microbiota in farmed Atlantic salmon with ulcerative disorders, raw sequence reads. 1 records from Microbial indicators of anthropogenic marine pollution identified by 16S and 18S metagenomic library analysis. 14 records from Estonian Museum of Natural History. 2 records from Biosphärenpark Wienerwald - Pfaffstätten. 739 records from Collection Crustacea - ZIM Hamburg. 37 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Belgica cruise BG86/1. 2 records from Riedkanal Bötzingen. 125 records from Resilience of Antarctic marine benthic invertebrates and the ecological consequences of environmental change - Amphipod Data 2002/10. 1 records from Colección Entomológica de Piedras Blancas. 16 records from Lizard Island Research Station. 2 records from Artenvielfalt der Nordsee - Sylt. 1 records from Kinderwald Hannover. 2534 records from Invertebrates of the Gothenburg Natural History Museum (GNM). 1 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 1545 records from BioChem: Davis Strait and Baffin Bay Zooplankton. 2898 records from NIWA Invertebrate Collection. 9 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 3 records from Natusfera Citizen Science Observation Dataset. 34 records from Water and Sediment samples Targeted loci environmental. 170 records from AM: Freshwater Invertebrates (1900-2005). 1 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 2108 records from Museum of Comparative Zoology, Harvard University. 1 records from A new species of Grandidierella Coutière, 1904, G. nioensis sp. nov. (Amphipoda, Aoridae), from the east coast of India. 1 records from Landschaftspark St.Leonhard-Deisendorf. 7 records from SIO_FAMIZ. 105 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 1 records from Umgebung des Spalatin Gymnasium Altenburg. 10 records from Biome of Australia Soil Environments. 68 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 1 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 74 records from RMT Trawl catch from the 2005/06 V3 BROKE-West voyage - Fish. 15 records from INNS Data: All Taxa (West Wales). 3 records from Diet analysis of Japanese sardine and Pacific round herring larvae. 308 records from Macrobenthos Chukchi Sea, 1986. 6 records from Invertebrates compiled by W.Block. 1 records from Abundance of benthos infauna at station GIK23004-3. 14 records from sediment metagenome Metagenome. 4 records from St Andrews BioBlitz 2015. 4836 records from Marine Offshore Seabed Survey data held by JNCC. 174 records from Abundance of the benthic infauna of the North Sea sampled during Victor Hensen cruise VH1486. 54 records from Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. 3 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 1020 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 6 records from Merseyside BioBank (verified). 1 records from A new species of Cyphocarididae (Crustacea, Amphipoda, Lysianassoidea) from off the northeastern Brazilian coast. 1 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 627 records from ZMMU MSU, White Sea Branch. 4 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 1 records from Biologische Station im Kreis Wesel. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Bachabschnitt der Nette (Osnabrück). 38 records from Données photographiques validées de la galerie du forum "Le Monde des Insectes". 1 records from Biotope in Rheine - Aktion 350. 9 records from Australian Institute of Marine Science (AIMS) - CReefs Ningaloo Reef Biodiversity Expedition, Australia (2008 - 2010). 30 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 6701 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 748 records from 1915-2016 Department for Environment Food & Rural Affairs (Defra), Marine Strategy Framework Directive (MSFD) Collation of invasive non-indigenous species. 1 records from Marine sediment metagenome ICM_CFU. 2 records from Bulau. 1 records from (Table B) Abundance of benthic fauna associated with shrimp swarms at hydrothermal fields on the Mid-Atlantic Ridge. 11 records from Zooplankton sampling in the coastal waters of south eastern Tasmania, Australia (2009-2015). 4 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1369 records from Tasmanian Natural Values Atlas. 1 records from Museu Darder de Banyoles. 89 records from University of Alberta Freshwater Invertebrate Collection (UAFIC). 5 records from A new genus and species of Aoridae (Amphipoda, Senticaudata), Propejanice lagamarensis gen. nov. sp. nov. from Brazil. 3439 records from Artportalen (Swedish Species Observation System). 4 records from Crustacean specimens of Bihoro Museum. 1 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 51 records from Greenland macrobenthos 2006. 8 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 2 records from Priest Pot species list, Cumbria, Britain. 1775 records from AxIOM: Amphipod crustaceans from insular Posidonia oceanica seagrass meadows. 388 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 12 records from sediment metagenome Raw sequence reads. 1 records from Impacts of crude oil and chemical dispersant exposure on marine microbial biofilm formation and steel corrosion. 675 records from MBON POLE TO POLE: SANDY BEACH BIODIVERSITY OF YUCATAN COAST. 193 records from ARMS Jeddah sample Raw sequence reads. 809 records from SEWBReC Myriapods, Isopods, and allied species (South East Wales). 6 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from Die Bachspezies. 218 records from BioFokus. 52307 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 31 records from CSIRO, Cruise SS200510, Benthic Biodiversity, Western Australia, 2005. 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1a. 4 records from Anymals+plants - Citizen Science Data. 8 records from DASSH Data Archive Centre volunteer sightings records. 6046 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 1 records from Tauchen und Meer. 1 records from Tartu University, palaeontology collections. 12 records from Benthos counted on dredged samples during Valdivia cruise VA44. 671 records from Benthos Chirnov Basin 1986 and 2002. 999 records from Queensland Museum provider for OZCAM. 3 records from Benthic macrofauna abundance of sediment core 13200-078. 66 records from Under-ice Amphipods in the Greenland Sea and Fram Strait (Arctic): Environmental Controls and Seasonal Patterns Below the Pack Ice. 27150 records from International Barcode of Life project (iBOL). 1 records from LBV 100 - Artenvielfalt am Rothsee. 2 records from Estonian University of Life Sciences. 5 records from Persianorchestia, a new talitrid genus (Crustacea: Amphipoda: Talitridae) from Gulf of Oman, Iran. 2 records from Macrofauna biomass in surface sediment sampled during cruise DI226. 2 records from A new species of Cephaloecetes (Bubocorophiina) from the Iranian coasts of the Gulf of Oman and the Hormuz Strait (Crustacea: Amphipoda: Siphonoecetini). 290 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 5 records from Four new species of Lysianassidae Dana, 1849 (Crustacea: Amphipoda) From Northeastern Brazilian coast. 4 records from 20 Jahre Naturschutzgebiet Dreienberg. 7 records from Talitrus saltator (Montagu, 1808), a species complex (Amphipoda, Senticaudata Talitroidea, Talitridae). 4 records from Macroinvertebrate abundance data from the littoral zone of a number of large New Zealand lakes. 9 records from Artenvielfalt der Nordsee - Helgoland. 1911 records from Macrobenthos monitoring at long-term monitoring stations in the Belgian part of the North Sea from 2001 on. 13 records from (Table 2b) Biomass of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 1 records from Stever. 14 records from Three new remarkable amphipod species (Crustacea: Gammaridae) from springs and subterranean waters of Central Asia. 5 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 7 records from Ice Amphipods Canada Basin. 159 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 13 records from (Table 2c) Percentages of energy flow of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 817 records from ZooplanktonBeaufortSeaNOGAP2. 321 records from FBIP: Offshore Benthic Macrofauna Data. 143 records from Zooplankton abundance and population structures assessed during April-September of 2001-2, Southern Ocean, GLOBEC. 18 records from Benthic Macroinvertebrate Diversity in the middle Doce river basin, Brazil. 1 records from SOLA Raw sequence reads. 8 records from Arthropod specimens of Natural History Museum, Kishiwada City. 1 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 1 records from Artenvielfalt rund um die Dalbek-Schule. 84 records from (Table A-2.1 to A-2.7) Abundance of macrobenthos in surface sediments in the Arctic Ocean. 1 records from Rediscovered syntypes of Procrangonyx japonicus, with nomenclatural consideration of some crangonyctoidean subterranean amphipods (Crustacea: Amphipoda: Allocrangonyctidae, Niphargidae, Pseudocrangonyctidae). 1 records from Artenvielfalt Kreis Gießen. 60 records from Siphonoecetini Just, 1983 (Crustacea, Amphipoda, Ischyroceridae) 13: Western Australian species of Bubocorophiina in Rhinoecetes, Cephaloecetes, Sinoecetes, Borneoecetes and Pararhinoecetes gen. nov.. 1315 records from Gwaii Haanas Invertebrates (OBIS Canada). 2 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 250 records from Zooplankton Abundance Based on Taxa and Life Stages or Size. 3 records from Bibliographique de la faune, la flore et la fonge de France métropolitaine et outre-mer. 6 records from The family Hyalidae (Crustacea: Amphipoda: Talitroidea) from Korean waters. 2. Genus Protohyale Bousfield & Hendrycks, 2002. 136 records from Galathea II, Danish Deep Sea Expedition 1950-52. 2 records from Macroalgas, equinodermos y crustáceos de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 1 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 1 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 1 records from Rifle sediment bacterial community Targeted Locus (Loci). 36 records from NCSM Non-molluscan Invertebrates Collection. 72 records from Midden-Limburg Fish Ponds Survey. 1 records from UF Florida Museum Paleobotany. 1 records from Abundance of benthos infauna at station POS128/2_281. 4 records from New Antarctic stenothoids sensu lato (Amphipoda, Crustacea). 61 records from Kyklades-data of the Central Aegean Sea. 2 records from Schussenaue bei Berg. 8 records from Invert Paleo Specimens. 1703 records from Hypogean macro-Crustacea records. 9 records from PondNet data 2012-2014. 871 records from ZooplanktonBeaufortSeaNOGAP1. 1 records from Wattenmeer-Safari (Wurster Watt). 172 records from IMOS - AusCPR: Zooplankton Abundance. 7765 records from imr_mareano_rpsledge. 1 records from Bremerhaven. 1363 records from DREAL_PACA_2017_12_18. 30 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 1214 records from Alien macro-invertebrates in Flanders, Belgium. 2 records from Pseudaeginella telukrimau sp. n., a new species of caprellid (Crustacea: Amphipoda) from Malaysia. 337 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE241. 1 records from Binsenwiesen. 97 records from Antarctic Biodiversity Studies 2006 (Ross Sea, Scott Island, and Balleny Islands) (TAN0602). 1 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 2 records from Zukünftiges NSG Höftland/Bockholmwik. 153 records from Survey data of tidal flats on the Monitoring sites 1000 project, BDCJ. 6 records from Vinogradovopleustes punctatum, new genus, new species, a pleustid amphipod from the Okhotsk Sea (Crustacea: Amphipoda: Gammaridea: Pleustidae: Pleusymtinae). 1 records from VSN-Wiese. 1 records from Abundance of benthos infauna at station GIK23055-1. 15 records from A review of Quadrimaera Krapp-Schickel & Ruffo, 2000 (Amphipoda: Senticaudata) from Brazil. 3 records from Marine Sightings & Miscellaneous Species Records from Natural Resources Wales (NRW), 2007 onwards. 247 records from Marine biological observation data from coastal and offshore surveys around New Zealand. 1 records from Wulfsmuehle/Pinnau. 20 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Unassessed data. 432 records from Biota occurrence data from plankton surveys around New Zealand. 2 records from Local BioBlitz Challenge 2013. 1 records from Triebesbach (Zeulenroda-Triebes). 480 records from Mesopelagic Community off the North Western Portuguese Coast between 1998 and 2000. 157 records from Diversidad bentónica de la laguna Celestún, Yucatán. 14 records from Yorkshire Wildlife Trust Shoresearch. 1 records from Tauchen und Meer 02. 4 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 10 records from A new family, genus and species of freshwater amphipod Australomicroprotopus megacoxa gen. nov. sp. nov. (Senticaudata, Corophiidea, Microprotopoidea, Australomicroprotopidae fam. nov.) from Australia. 21 records from Grand Manan Basin Benthos. 1180 records from BIOLOGICAL SCIENCES DATA. 5 records from A new species of genus Parhyale Stebbing, 1897 (Crustacea, Amphipoda, Hyalidae) from Gujarat State, India. 238 records from Further investigations of the effects of the Nella Dan oil spill 1988/94. 1 records from Unna-Mühlhausen, Wiesen. 123 records from International Polar Year and Census of Antarctic Marine Life Ross Sea voyage (TAN0802) biodiversity data. 18 records from Carnarvon Basin Wetland Invertebrate Survey. 14 records from Isle of Man historical wildlife records 1990 to 1994. 1 records from UAM Fish Collection (Arctos). 8 records from TWIC Biodiversity Field Trip Data (1995-present). 1 records from 2. Aspacher GEO-Tag der Artenvielfalt. 2 records from Megafaunal data from the 2009 BIOFUN trans-Mediterranean deep-sea cruise. 1 records from Benthic macrofauna abundance of sediment core 13077-098. 3 records from Eukaryote diversity assessment of sediments of the Western English Channel. 18 records from Essig Museum of Entomology. 3 records from A new species of Victoriopisa bantenensis (Crustacea: Amphipoda: Eriopisidae) from West Java, Indonesia. 106 records from Natural Resources Wales Regional Data : Mid-Wales. 75 records from Auburn University Museum of Natural History Invertebrates. 285 records from River Biologists' Database (EPA). 18 records from Invertebrate specimens in the Wakayama Prefectural Museum of Natural History, Japan.. 26 records from Crustáceos estomatópodos, anfípodos, isópodos y decápodos del litoral de Quintana Roo. 1 records from A new species of Nuuanu (Crustacea, Amphipoda, Nuuanuidae) from a Caribbean coral reef with identification keys to males and females of Nuuanu species. 30 records from New talitrids from South Africa (Amphipoda, Senticaudata, Talitroidea, Talitridae) with notes on their ecology. 273 records from Collections and observation data National Museum of Natural History Luxembourg. 6219 records from Lund Museum of Zoology (MZLU). 109 records from Saisie des bulletins de la Société Linnéenne de Bordeaux (2013 > 2015). 39 records from (Table 2) Median abundances of macrobenthos in surface sediments. 1 records from 16S data describing Antarctic benthic sediment. 39 records from California Current Cruise CCE-P1408 Process Cruise #6. 6 records from Protist Diversity in the East China Sea. 3 records from A new species of the genus Elasmopus from Miyako Island, Japan (Crustacea: Amphipoda: Maeridae). 311 records from Merseyside BioBank (unverified). 1301 records from NBIS Records to December 2016. 29 records from COLETA - IMAR/DOP-Uac reference collection from 1977 to 2012. 1 records from Rohrmeistereiplateau und angrenzendes Gebiet. 85 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 11 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 27 records from South American Antarctic Marine Biodiversity Literature. 58 records from Stoke-on-Trent Environmental Survey results (1982-1984). 1 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 1 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 6066 records from DEMNA-DNE : Occurrences of benthic macroinvertebrates in running waters of Wallonia, Belgium. 5 records from Marine Data from The Wildlife Trusts (TWT) Dive Team; 2014-2017. 17 records from (Table A) Wet weight night biomass of dominant mesozooplankton groups obtained from night catches within the Bismark Polygon in June 2001 and June-August 2002. 73 records from Données BioObs - Base pour l’Inventaire des Observations Subaquatiques de la FFESSM. 1 records from Marine metagenome ICM_AWP. 207 records from RMT Trawl catch from the 1982/83 V2 ADBEX I voyage. 1 records from BÜG. 29 records from The pre-winter 2007 vertical distribution of zooplankton in the Cape Bathurst and North Water polynyas, and Lancaster Sound, Canadian Arctic. 56 records from Colección Zoológica de la Universidad del Tolima (CZUT) - Macroinvertebrados. 1 records from Vergleich der Fauna eines naturbelassenen mit einem wasserwirtschaftlich veränderten Gewässer. 17 records from Modernisation des ZNIEFF du PnrL. 63 records from (Table 4) Abundance of under-ice amphipods on flat ice and ice ridges sampled during the 2005 Hidden Ocean expedition. 26 records from Three new species of Colomastix Grube, 1861 (Amphipoda: Colomastigidea) from Todos-os-Santos Bay, northeastern Brazilian coast, with identification keys to Atlantic Ocean species. 261 records from National River Water Quality Network Database (Macro-invertebrates). 3 records from Coastal and Marine Species Database. 102 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 3 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 1 records from Saltern of Margherita di Savoia Metagenome. 3 records from Environmental eukaryotes Metagenome. 47 records from Healthy Waterways Waterwatch Program. 36 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 2 records from South Caribbean Diversity. 1 records from Benthic macrofauna abundance of sediment core 13200-051. 308 records from Monitoring data from the federal state Saxony (Germany). 37 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 1 records from Benthic macrofauna abundance of sediment core 12930-028. 2 records from Códigos de barras de la vida en peces y zooplancton de México. 1 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 257 records from New Zealand Arthropod Collection (NZAC). 111 records from Rådgivende Biologer. 597 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE262. 1737 records from imr_mareano_beamtrawl. 806 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 1 records from Effects of organic matter manipulation on archaeal, bacterial, and fungal community assembly. 112 records from Marine Invertebrate from Argentina, Uruguay and Chile. 4 records from Groundwater amphipods (Crustacea, Malacostraca) of India, with description of three new cavernicolous species. 1412 records from Sustainable Rivers Audit. 648 records from Marine flora and fauna records from the North-east Atlantic. 2226 records from Marine Records from Pembrokeshire Marine Species Atlas. 1 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 1 records from Abundance of benthos infauna at station PS1241-1. 32603 records from England Non Native Species records 1965 to 2017. 1 records from marine metagenome Raw sequence reads. 266 records from Asia-Pacific Dataset. 607 records from Tasmanian Museum and Art Gallery provider for OZCAM. 1020 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 4826 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 904 records from UAM Invertebrate Collection (Arctos). 2 records from Heider Bergsee (Brühl). 4 records from GEO-Hauptveranstaltung in "Wildtierland". 1439 records from JODC Dataset. 17 records from Zooplankton Abundancies White Sea, 1972. 272 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Macros. 533 records from Welsh Invertebrate Database (WID). 338 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 457 records from IndOBIS, Indian Ocean Node of OBIS. 52 records from Biodiversidad selecta de los humedales de Laguna de Términos - Pantanos de Centla. 16 records from Hermesorchestia alastairi gen. et sp. nov. from Australia (Talitridae: Senticaudata: Amphipoda: Crustacea). 2 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/356-1. 182 records from Invertebrate Site Register - England (1738-2005).. 14 records from IMOS National Reference Station (NRS) - Zooplankton Abundance. 101 records from kerkyra. 200 records from Macrobenthos and Meiobenthos Tuktoyaktuk Harbor and Mason Bay 1985-1988 NOGAP. 1 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 905 records from Collection Crustacea SMF. 1 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 1 records from Abundance of benthos infauna at station GIK23037-3. 2 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 63 records from Bentos collection of the Museum of Nature and Human Activities, Hyogo. 381 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 17 records from Isle of Man historical wildlife records 1995 to 1999. 1 records from Brenz (Heidenheim). 11 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 88 records from INNS records held by BIS in Powys and Brecon Beacons National Park. 2 records from Spelaeogammarus uai (Bogidielloidea: Artesiidae): a new troglobitic amphipod from Brazil. 530 records from Crustacean collection of the National Museum of Nature and Science. 14 records from Records of Invasive Non Native Species held on the Cofnod database. 4 records from Matter enrichment of the macrofauna community of MAC station 13200-005. 326 records from BRERC species records within last 15 years. 1062 records from Limnic freshwater benthic invertebrates biogeographical mapping/inventory NTNU University Museum. 241 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE272. 9 records from Microbial eukaryote 454 Roche sequencing in estuarine ecosystems. 16 records from Stable isotope data from marine sediment and invertebrates from Davis Station 2009/10. 4 records from GEO-Hauptveranstaltung (Duisburg). 11 records from Macrofauna abundances from mesocosm experiments at eastern and western branches of the Whittard canyon. 9 records from 70 samples data of Kiel Bay. 20 records from Données naturalistes de Xavier JAPIOT. 1424 records from Amplicon sequencing of Tara Oceans DNA samples corresponding to size fractions for protists.. 455 records from Catálogo de las especies de crustáceos anfípodos invasores del Parque Nacional Sistema Arrecifal Veracruzano (PNSAV) y la actualización de la base de datos (CONABIO) de los anfípodos en México. 10 records from Greenland Macrobenthos Young Sound, 1996. 7859 records from Marine data from Natural Resources Wales (NRW) Technical Support (Research & Monitoring) Contracts, Wales. 50 records from BioFresh Pond Data. 1 records from White sea picoplankton Metagenome. 2289 records from Macrobenthos monitoring in function of aggregate extraction activities in the Belgian part of the North Sea. 986 records from Marine Intertidal Phase 1 Species Dataset from the Countryside Council for Wales 1996-2005. 475 records from WhiteSeaPlankton. 990 records from Monitoring data from the federal state Bavaria (Germany). 3 records from Marine sediment metagenome ICM_DSE. 12 records from All taxa records for Leicestershire and Rutland between 1987 and 2016. 1046 records from Continuous Plankton Recorder Dataset (SAHFOS). 643 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during HEINCKE cruise HE133. 1866 records from ZUEC-CRU - Coleção de Crustacea do Museu de Zoologia da UNICAMP. 1 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 1 records from Additional records of Elasmopus vachoni Mateus & Mateus, 1966 (Crustacea: Amphipoda: Maeridae) from European waters (Tarifa, southern Spain). 1 records from Tiergarten Straubing. 2 records from Parc_National_des_Ecrins_2017_12_18. 1 records from Landwehrbach. 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 2 records from Stausee (Oberdigisheim/Meßstetten). 1193 records from Northern Territory Museum and Art Gallery provider for OZCAM. 3 records from Abundance of benthos infauna at station GIK23002-1. 1 records from Erzental (Oberotterbach). 7 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Walther Herwig cruise WH220. 37948 records from DASSH Data Archive Centre - Statutory Surveys. 1 records from Listhof und Umgebung. 11 records from Biology and Ecology of Cryopelagic Amphipods from Arctic Sea Ice Collected near Franz Josef Land in the summer of 1994. 19 records from Antarctic Marine Species Sequence Data. 2 records from Wupperaue bei Kemna (Wuppertal). 26 records from The Ecology and Biogeography of Heard Island Marine Benthos 1987/88. 28 records from Gulf of Gdansk. 13 records from Museu Paraense Emílio Goeldi - Diptera Collection. 136 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 2 records from Abundance of benthos infauna at station GIK23038-1. 7232 records from Invertebrate Zoology Division, Yale Peabody Museum. 16 records from Merseyside BioBank Active Naturalists (unverified). 5 records from Bird Collection of Museum and Institute of Zoology PAS. 1 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 5 records from Palaeozoological Collections (PZ), Swedish Museum of Natural History (NRM). 49 records from Benthic macrofauna abundance and biomass in surface sediment during cruise CD86. 18 records from Données "faune" de l'Agence des Espaces Verts (AEV) pour le SINP île de France. 36 records from Yorkshire Naturalists Union Marine and Coastal Section Records. 1 records from Species within North Ayrshire from 1984 - Present. 1 records from Naturalis Biodiversity Center (NL) - Porifera. 165 records from Zooplankton monitoring in the Belgian Part of the North Sea between 2009 and 2010. 113 records from Monitoring data from the federal state Berlin (Germany). 3 records from Weser und Weseraue bei Höxter, Godelheim und Boffzen. 462 records from RNF - Données de l'association Vivarmor Nature. 79 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 151 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 427 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage. 8 records from Two species of Ceradocus collected from coastal areas in Japan, with description of a new species (Crustacea: Amphipoda: Maeridae). 75 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage. 955 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 2 records from Radnorshire Wildlife Trust records held by BIS. 3 records from Macrofauna biomass in surface sediment sampled during cruise DI237. 479 records from Macrobenthos monitoring at long-term monitoring stations in the Belgian part of the North Sea between 1979 and 1999. 3 records from Tag der Artenvielfalt. 41 records from Four new species of Cymadusa Savigny, 1816 (Amphipoda: Ampithoidae) and new records of C. filosa Savigny, 1816 from Brazilian coast. 38 records from Invertebrate records from sites that are mainly across Scotland. 1 records from Wirbach-Taubental (Bad Blankenburg). 1 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 2 records from Colección de Insectos de la Universidad del Quindío (CIUQ). 15 records from NRW Regional Data: North Wales. 258 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions. 344 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE275. 211 records from LERN Records. 53 records from Miscellaneous records held on the Cofnod database. 1 records from Abundance of benthos infauna at station POS128/2_284. 1 records from iRecord Surveys. 1 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 15 records from ZINRAS_Arctic_Benthos. 3 records from MAL. 31826 records from Australian Museum provider for OZCAM. 1 records from FFH-Gebiet Paartal. 1 records from Schulprojekt (Bremen). 1 records from On some Haploops species collected in the North Atlantic Ocean with the description of Haploops islandica n. sp. (Crustacea: Gammaridea: Ampeliscidae) [Contribution to the knowledge of the Haploops genus. 8.]. 1 records from Grünes Germersheim. 74 records from Rhodolith Beds in Northern New Zealand: Characterisation of Associated Biodiversity. 3287 records from DASSH Data Archive Centre Academic Surveys. 2 records from Brigham Young University Arthropod Museum. 9 records from Diet analysis of Pacific Bluefin Tuna larvae. 18 records from Species Composition and Abundance of Zooplankton in the Nearshore Beaufort Sea in Winter-Spring 1978-1980. 19 records from Nekton and plankton counts from bongo net (300, 500 µm) hauls of cruise GAE 1975/76. 4 records from Two new species of groundwater amphipods of the genus Niphargus Schiödte, 1849 from northwestern Iran. 2 records from Erlengraben/Lipp-Tal (Östringen). 7 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 391 records from Macrobenthos monitoring in function of the Water Framework Directive in the period 2007-2009. 1 records from Nationalpark Jasmund. 285 records from Benthic communities and environmental parameters in Amvrakikos Wetlands: Mazoma, Tsopeli,Tsoukalio, Rodia and Logarou lagoons (September 2010 – July 2011). 12492 records from Natural History Museum (London) Collection Specimens. 1 records from AKG-Gelände (Bensheim). 1 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 35 records from On the composition of the benthic fauna of the western Fram Strait. 8 records from A new caprellid species (Crustacea: Amphipoda: Senticaudata) from Brazil. 1080 records from Cawthron Institute freshwater invertebrate data. 205 records from Seasearch Marine Surveys in Wales. 2 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 8 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 1 records from Jordal. 52 records from Crustacea ZMK. 7 records from Ice Amphipods Svalbard, 2000. 11 records from Zooplankton Abundance_Umbrella net_sea ice zone 2007/12. 31 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Tridens00/5. 6 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 36 records from The Ecology of the Inshore Marine Zooplankton of the Chukchi Sea near Point Barrow, Alaska. 283 records from Antarctic Amphipoda. 232 records from Biological Reference Collections ICM CSIC. 6 records from Nanticoke Harbour, ON, Canada (plankton SSU 454 sequencing). 14 records from Tab. 6: Relative Abundanz einzelner Arten der Endofauna. 12363 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 799 records from Monitoreo Ambiental del Proyecto La Colosa. 179 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 8 records from Meiobenthic assemblages colonizing artificial soft sediments at 20 m depth in Arctic glacial Kongsfjorden, Spitsbergen, Svalbard - individual number. 4630 records from CAS Invertebrate Zoology (IZ). 1 records from NCSM Invertebrate Paleontology Collection. 1 records from Tag der Artenvielfalt im Taubental. 1 records from A Method for Studying Protistan Diversity Using Massively Parallel Sequencing of V9 Hypervariable Regions of Small-Subunit Ribosomal RNA Genes. 5 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 1 records from Abundance of benthos infauna at station GIK23071-1. 3 records from FBIP:Invertebrates community dynamics in temporary wetland ecosystems. 1 records from Selz (Ingelheim am Rhein). 124 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 1 records from New genus and species of the family Niphargidae (Crustacea: Amphipoda: Senticaudata), Chaetoniphargus lubuskensis gen. nov., sp. nov. from Croatia. 2 records from Dalbekschlucht. 1 records from An der Ohm, (Wettsaasen). 2 records from "Schule am Inselsee" Güstrow. 98 records from SA Fauna (BDBSA). 2 records from Kohlstattbrunnental. 9 records from A redescription of Leucothoe spinicarpa (Abildgaard, 1789) based on material from the North Atlantic (Amphipoda: Leucothoidae). 1246 records from CNCR/Colección Nacional de Crustaceos. 1 records from Exkursion in der Ehrbachklamm/ an den Erbach. 4 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 9 records from Invertebrates (except insects), Outer Hebrides. 37 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 39 records from Zooplankton Bering Strait Tiglax 1991. 48 records from Miscellaneous records held by BIS. 16 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 2 records from Cold-water corals off Angola as refuge for a new Aeginella species (Crustacea: Amphipoda: Caprellidae). 6630 records from Norwegian Biodiversity Information Centre - Other datasets. 1 records from Werremündung im Schwarzatal. 11 records from BOEM Beaufort Sea, Alaska, Fish and Invertebrate Haul and Catch, with Oceanography, 2008. 1 records from Feriendorf Ober-Seemen. 1 records from Langes Tannen. 2 records from Microbial eukaryotes present in a Norwegian coastal ecosystem and in the gut content of Calanus copepods from Raunefjorden. 1 records from Ascidian and Seawater Metagenome. 826 records from REDIT 1. 2 records from Microbial communities in estuarine sediments. 2 records from Antarctic and New Zealand Byblisoides (Amphipoda: Ampeliscidae) with a key to the world species. 161 records from Data from Defra Family Organisations supplied to Staffordshire Ecological Record. 314 records from ecoscope_observation_database. 2 records from Metagenome microbial communities of bottom sediments of the Kara Sea. 3610 records from imr_mareano_grab. 1036 records from NatureServe Network Species Occurrence Data. 6 records from ALA species sightings and OzAtlas. 4788 records from Abundance and diversity of the Amphipoda (Crustacea) from the Greenlandic shelf. 107 records from Temporal evolution of zooplankton, surface observations, in the Northwestern Mediterranean Sea, Villefranche-sur-mer 1898-1917. 254 records from Subtidal hyperbenthos monitoring in function of a foreshore suppletion at the Belgian coast, period 2013-2016. 1 records from Erft in Selikum (Neuss). 5 records from Macrofauna abundance in surface sediment sampled during cruise DI222/2. 3 records from (Table 4) Fauna composition of the community of Nephtys ferruginea - Amphiura acrystata in bottom sediments from the shelf edge in the California upwelling zone. 2448 records from Azorean Biodiversity Portal. 1781 records from Ant'Phipoda Database (New records). 109 records from Non-vertebrate Paleontology, Jackson School Museum of Earth History, University of Texas at Austin. 1894 records from Marine metagenomes Metagenome. 200 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 9 records from Red Sea microbial plankton Raw sequence reads. 39 records from Colección de Zoología Invertebrados - Carcinología. 1 records from ATBI Parc national du Mercantour / Parco naturale Alpi Marittime. 44 records from Marine Water Column Samples Targeted loci environmental. 28 records from Données naturalistes de CERCOPE (Jean-Louis PRATZ). 75 records from BugGuide - Identification, Images, & Information For Insects, Spiders & Their Kin For the United States & Canada. 28 records from SER Site-based Surveys. 364 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE255. 54 records from MBON POLE TO POLE: SANDY BEACH BIODIVERSITY OF BARRA DEL CHUY, URUGUAY. 3 records from A new data of freshwater amphipod of genus Niphargus Schiödte, 1849 from Lorestan Province in Iran. 3 records from Benthic macrofauna abundance of subcores of sediment core 13200-073. 697 records from MDFRC macroinvertebrate survey. 25 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 1 records from (Table A) Abundance of species detected in mussel beds within hydrothermal fields on the Mid-Atlantic Ridge. 2 records from Beisetal bei Niederbeisheim. 8 records from GEO-Hauptveranstaltung Bodden (Vilm). 1 records from Grundwasserlebensraum im Englischen Garten (München). 144 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 79 records from EMOSE (2017) Inter-Comparison of Marine Plankton Metagenome Analysis Methods. 2 records from Perchtoldsdorfer Heide. 1 records from Field Museum of Natural History (Geology) Fossil Invertebrates Collection. 266 records from Nekton and plankton counts from RMT (4500 µm) hauls of cruise GAE 1975/76. 76 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 1 records from Mooswald (Freiburg). 51 records from Plankton&BenthosResearch. 2 records from Structuring effect of environmental variables on protistan diversity patterns in two anoxic marine basins. 7 records from Abundance of benthos infauna at station GIK23011-2. 1 records from SAR amplicon from community incubated with various nanophytoplankton in microcosm. 123 records from (Table 4) Biomass of (benthic) amphipods in the Bering and Chukchi seas. 3 records from sediment metagenome Metagenome. 1 records from Bayerische Donau - Riedlingen. 283 records from Norwegian Species Observation Service. 2 records from PlutoF platform reference-based occurrences. 1 records from Ocean sediment-basement interface Targeted Locus (Loci). 434 records from BIOMAERL.Maerl Biodiversity.Functional Structure And Antropogenic Impacts (1996-1998).. 594 records from Données RNN LPO. 15419 records from Marine benthic dataset (version 1) commissioned by UKOOA. 4 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 888 records from Manscape. 1 records from City of Edinburgh Natural Heritage Service - Ranger Ad-hoc records and sightings. 2 records from Environment Agency Rare and Protected Species Records. 6 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 1 records from Distribution of meiobenthos in sediment core M19_246-2 of the northeastern Atlantic (Table 1). 3 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 2 records from Review of amphipods of the genus Cryptodius Moore, 1992 (Amphipoda: Ochlesidae) from the coastal waters of Sakhalin Island (Far East of Russia). 1 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 53 records from CSIRO Survey TT200801 - ROV Jason cruise tn228: South and East of Tasmania. 204 records from Crustáceos macrobénticos de la plataforma y talud continental del Golfo de México. 2 records from Canadian Museum of Nature Fossil Vertebrate Collection. 1 records from Stadtpark Sulzbach-Rosenberg. 64 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 31 records from Naturalis Biodiversity Center (NL) - Museum collection digitized at storage unit level. 1 records from The rare deep-living hyperiid amphipod Megalanceoloides remipes (Barnard, 1932): complementary description and symbiosis. 3 records from BUND - Dassower See (Lübeck/Dassow). 19 records from Crustacean specimens of Kaizuka City Museum of Natural History. 153 records from Collection Crustacea - SNSD. 3 records from Naturschutzgebiet Kochertgraben. 647 records from Marine sites, habitats and species data collected during the BioMar survey of Ireland.. 58 records from Composition and distribution of the biomass of zooplankton in the central Arctic Basin 1975, 1976, 1977. 276 records from Marine invertabrate(ARTHROPODA) specimen database of Osaka Museum of Natural History. 4 records from Fish catch from 1996/97 Voyage 1 WASTE (WOCE Antarctic Southern Transect Expedition). 6 records from Environmental zooplankton Targeted Locus (Loci). 39 records from (Table 3) Median biomasses of macrobenthos in surface sediments. 15794 records from Diversidad bentónica del ambiente intermareal e infralitoral somero de Progreso, Yucatán. 122 records from 2004-2012 Bishop et al. Occurrence of non-native sessile invertebrates on the English coast. 306 records from BRERC species records recorded over 15 years ago. 26 records from The near-bottom plankton and benthic invertebrate fauna of Josephine and Great Meteor Seamounts (Table 2). 24 records from Hydrate Ridge, OR - Deep sea cold seep ecosystem Targeted Locus (Loci). 2 records from Hatikka Observation Database. 3 records from Scientific Results of the New Zealand Government Trawling Expedition, 1907. 429 records from Données d'occurrences Espèces issues de l'inventaire des ZNIEFF. 2 records from PIKE – Distribution, extinctions and introductions of freshwater fish in Sweden. 12 records from Diveboard - Scuba diving citizen science observations. 1 records from Bäche im Mooswald (Vörstetten). 2 records from Ghent University - Zoology Museum - Insect collection. 12 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 27 records from Staying cool also has consequences: increased sea ice cover disrupts food web structure in East Antarctica-Data. 7938 records from Inland water macroinvertebrate occurrences in Flanders, Belgium. 1 records from Biodiversidad en el valle de Cuatro Ciénegas.. 41 records from Nutrient addition mesocosm experiment Targeted Locus (Loci). 2 records from Eukaryotic natural population from Northern Baffin Bay - Raw sequence reads. 3 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 2 records from Red Sea Leucothoidae (Crustacea: Amphipoda) including new and re-described species. 4 records from Canada_BasinMegabenthos2002. 787 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 8979 records from Geographically tagged INSDC sequences. 2014 records from Bernice P. Bishop Museum. 13052 records from Natural England Marine Monitoring surveys. 10 records from WTSWW Data: All Taxa (West Wales). 2 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 2 records from "Ahrschleife bei Altenahr". 7638 records from Crustaceos del Museo de Ciencias naturales de la Universidad Simón Bolívar. 667 records from Ross Sea Biodiversity Survey 2004 (BioRoss). 1335 records from South Australian Museum Australia provider for OZCAM. 60 records from Seasearch Marine Surveys in Ireland. 1104 records from Rockfish Recruitment and Ecosystem Assessment Survey, Catch Data. 19 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 181 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986. 1968 records from Actualización de la base de datos y la colección de hipéridos (Crustacea) y sifonóforos (Cnidaria) del Atlántico mexicano. 17 records from RMT Trawl catch from the 1983/84 V5 ADBEX II voyage. 336 records from SIO Benthic Invertebrate Collection. 1609 records from Marine Species Records from Skomer Marine Conservation Zone (MCZ) Marine Monitoring Programme. 34 records from DASSH Data Archive Centre volunteer survey data. 1 records from Macro-invertebrados de la cuenca alta y media del río Bita, Vichada (Colombia). 1 records from Unter hellen Zinnen und finsteren Grotten. 1 records from Schlichemquelle (Tieringen/Meßstetten). 4 records from Niphargus diadematus sp. n. (Crustacea, Amphipoda, Niphargidae), an inhabitant of a shallow subterranean habitat in South Moravia (Czech Republic). 21 records from CSIRO, Cruise SS200702, Marine Biodiversity Survey, Southeast Australia, 2007. 13 records from Systematic list of benthic invertebrates identified in the Heard Island and McDonald Islands region from 129 beam trawl or epibenthic sled samples 2003/08. 701 records from Marine Biological Sample Database, JAMSTEC. 341 records from Observation.org, Nature data from the Netherlands. 252 records from Nekton and plankton counts from RMT (320 µm) hauls of cruise GAE 1975/76. 6 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 3 records from Type material housed in the Carcinological Collection of the Museo de La Plata, Argentina. 70 records from Biodiversidad de crustáceos dulceacuícolas del centro de Nuevo León y noroeste de Tamaulipas (R53, Río San Juan y Río Pesqueria). 1 records from Abundance of benthos infauna at station GIK23017-1. 4 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 5144 records from Collection Crustacea - ZMB. 1 records from Observations.be - Non-native species occurrences in Wallonia, Belgium. 1 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 9 records from Avon Baselining - Invertebrates. 5 records from Schatzinsel Norderney. 1 records from NSG Dellwiger Wald, Dortmund. 3010 records from Monitoring data from the federal state Hesse (Germany). 127 records from INNS Data: All Taxa (South East Wales). 1 records from A new genus and species of Ingolfiellidae (Crustacea, Ingolfiellida) from the hyporheic zone in the Sierra de la Ventana, and its biogeographic relevance. 1503 records from NINA Vanndata øvrige arter. 5 records from A new species of the Hyalella ‘ azteca’ complex (Crustacea: Amphipoda: Hyalellidae) from Florida. 65 records from Colección General de Invertebrados del Cenpat (CNP-INV). 7 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 141 records from LERN Invasive Non-native Species Records. 11 records from Brecknock Wildlife Trust records held by BIS. 50 records from CASES: The pre-winter assemblages of southeastern Beaufort Sea. 332 records from Biodiversidad de macroinvertebrados bénticos de la región marina Tijuana-Ensenada Baja California, México. 1 records from Rur. 2 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 518 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE258. 560 records from USGS Nonindigenous Aquatic Species database. 1 records from Description of a widely distributed but overlooked amphipod species in the European Alps. 588 records from Benthic amphipods from Alacranes Reef, Campeche Bank, Mexico. 1 records from Données naturalistes de Pierre NOEL (M2MNHN). 9 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 49 records from European Molecular Biology Laboratory Australian Mirror. 1 records from St Andrews BioBlitz 2014. 32 records from Upper Murrumbidgee Waterwatch. 1 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 1 records from Kaulsdorf. 1 records from Dellwiger Bach (Dortmund). 2 records from Montgomeryshire Wildlife Trust records held by BIS. 2186 records from Invertebrates excl. Entomology at the Natural History Museum of Denmark. 295 records from Subtidal macrobenthos monitoring in function of a foreshore suppletion at the Belgian coast, period 2013-2016. 36269 records from NMNH Extant Specimen Records. 2 records from Draubiotop Lavamünd. 6 records from Two new Gammarus species and a new name (Crustacea: Amphipoda: Gammaridae) from Northwest China. 63 records from Extracellular DNA marine sediment Targeted Locus (Loci). 6 records from Sediment of acid mine drainage Targeted loci environmental. 1 records from Isartal Dingolfing. 5 records from Macrofauna abundance in surface sediment sampled during cruise DI231. 20106 records from Museums Victoria provider for OZCAM. 1 records from Biotope auf dem Gelände der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 29 records from Questagame weekly feed. 91 records from UMZC Zoological Specimens. 9 records from Epimeria cleo sp. nov., a new crested amphipod from the Ross Sea, Antarctica, with notes on its phylogenetic affinities (Crustacea, Amphipoda, Eusiroidea, Epimeriidae). 4 records from Macrofauna abundance in surface sediment sampled during cruise DI226. 14 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 1 records from Wasser-Lernort Nettemündung. 113 records from Survey of benthic and other marine invertebrates of Prydz Bay, 1990/91 Voyage 6. 1 records from MfN - Fossil vertebrates III. 14 records from Mariana and Kermadec Trench sediment 16S rRNA gene sequencing. 5 records from A new species of sponge-dwelling amphipod, Polycheria spongoteras sp. nov., from Spirits Bay, Northland, New Zealand. 1 records from Las colecciones del Museu Valencià d'Història Natural. 4 records from Gammaropsis elvirae sp. nov., a widely distributed amphipod (Amphipoda: Photidae) in the Yucatan Shelf, with ecological comments and a key for the genus in tropical America. 3711 records from Marine invertebrate collection NTNU University Museum. 31 records from Zooplancton en Bahia Magdalena, Baja California Sur, Mexico. 4 records from A new species of Quadrivisio (Amphipoda, Maeridae) from coastal tropical lagoons (Benin, West Africa). 149 records from Bay of Fundy Species List. 3 records from Macrofauna biomass in surface sediment sampled during cruise DI229. 6 records from Macroalgae of the Balleny Islands and western Ross Sea, Southern Ocean. 5 records from Recent Invertebrates Specimens. 11 records from Reptilia Collection of Museum and Institute of Zoology PAS. 38 records from Données bibliographique de la base BOMBINA. 2 records from LNHG Biological Records Dataset. 5 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 48 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 1 records from Pilstingermoos. 267 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE278. 2 records from MSB Parasite Collection (Arctos). 2 records from Benthic macrofauna abundance of subcores of sediment core 12930-065. 1 records from Bachpatenschaft Beeke. 647 records from Marine sites, habitats and species data collected during the BioMar survey of Ireland.. 2 records from Two new species of Hyalella (Crustacea, Amphipoda, Hyalellidae) from state of Rio Grande do Sul, Southern Brazil. 57 records from Ireland's BioBlitz. 3 records from Artenvielfalt auf den Elbwiesen (Dessau). 75 records from Polish Arctic Marine Programme. 3 records from Abundance of benthos infauna at station GIK23024-1. 18 records from Carnarvon Basin (Aquatic Projects) - Invertebrates. 25 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 3 records from Macrofauna biomass in surface sediment sampled during cruise DI222/2. 9 records from (Table B) Fauna associated with Bathymodiolus azoricus mussel beds within the Lucky Strike hydrothermal field, Mid-Atlantic Ridge. 1 records from Naturschutzgebiet Börstig bei Hallstadt. 5 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 14 records from Seasearch Marine Surveys in the Channel Islands. 4 records from How much do we know about marine metazoan biodiversity? Recent disclosures using second generation sequencing.. 120 records from Laptev Sea and Nansen Basin Zooplankton, 1993. 310 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 5 records from Macrofauna abundance in surface sediment sampled during cruise DI229. 4 records from Confirmation of Caprella scauroides Mayer, 1903 (Crustacea: Amphipoda) from New Zealand, using integrative techniques. 8 records from First record of the suborder Colomastigidea (Amphipoda) from Brazilian waters, with description of a new species of Colomastix Grube, 1861. 1 records from Schulhof A.-Lindgren-Schule (Elmshorn). 179 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 5460 records from Fish and zooplankton from RMT-8 net hauls on the BROKE voyage. 9 records from Nivå Bay species list, Zealand, Denmark. 6 records from Collection Crustacea - PUM. 14 records from Meiobenthos nSSU metagenetic meiobenthic data. 25 records from The talitrid amphipod genus Talorchestia from the South China Sea to the Indonesian Archipelago (Crustacea, Senticaudata). 1 records from Mangfalltal. 5886 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 271 records from River macroinvertebrate data for 2005 and 2006. 243 records from Wetland Invertebrate and Environmental Data 2010 Sampling Events. 12 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG93. 450 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 12009 records from Arctic Ocean Diversity. 5 records from Catch data from New Zealand research trawls since 2008. 2 records from North Marine Region demersal fish and invertebrate collection records (DEW collation), Australia (1980 - 1997). 2 records from Hamberger Brücke / Würmtal (Pforzheim). 33 records from CASES2003_2004. 2 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 44 records from Inventaire des Invertébrés marins de la Réserve Naturelle Nationale de Saint-Martin. 2 records from DASSH Data Archive Centre expert sightings records. 427 records from Development and validation of a multi-trophic metabarcoding biotic index for benthic organic enrichment biomonitoring using a salmon farm case-study.. 33 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 2 records from Données naturalistes de Pierre NOEL (pnoel). 3 records from Données de l'Observatoire de la Faune de Bourgogne. 2 records from Abundance of benthos infauna at station PS1239-1. 1 records from UNM Earth Sciences Collection (Arctos). 1142 records from Limnodata. 45 records from CSIRO, Cruise SS199701, Marine Biological Survey, South Tasmania, Southeast Australia, 1997. 3 records from Sediment Metagenome Raw sequence reads. 114 records from Expédition Karubenthos 2012 : inventaire des Mollusques et des Crustacés de la Guadeloupe. 394 records from RMT Trawl catch from the 1995/96 V4 BROKE voyage. 53 records from Temporal evolution of zooplankton by Regent net in the Northwestern Mediterranean Sea,Villefranche-sur-mer, 1959-2010.. 7 records from Two new species of Cerapus (Crustacea: Amphipoda: Ischyroceridae) from the Northwest Atlantic and Gulf of Mexico. 1 records from Censo de biodiversidad marina Edo. Miranda. 653 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 517 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 24 records from Zoology (Museum of Evolution - Uppsala). 22 records from Review of amphipods of the Melita group (Amphipoda: Melitidae) from the coastal waters of Sakhalin Island (Far East of Russia). III. Genera Abludomelita Karaman, 1981 and Melita Leach, 1814. 27 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Day/night stratified zooplankton sampling onboard the Norwegian R/V Jan Mayen. Program ALV. 3 records from Prince Edward Island marine metgenome Raw sequence reads. 1 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 1 records from Collection Crustacea - ZSRO. 9 records from Naturalis Biodiversity Center (NL) - Cnidaria. 4 records from Polymetallic nodule field Targeted loci environmental. 1304 records from Royal BC Museum - Invertebrates Collection. 1 records from NSG Karwendel. 23 records from Caprellidae (Crustacea: Peracarida: Amphipoda) from deep-sea waters off Galicia (NW Iberian Peninsula) with the description of a new genus and three new species. 311 records from UAM Insect Collection (Arctos). 60 records from NORFANZ Biological Survey, Tasman Sea, Australia - New Zealand 2003. 1 records from Kindergarten. 2 records from Biodiverskripsi: Biodiversity Theses Database. 318 records from Biodiversity Research and Teaching Collections - TCWC Marine Invertebrates. 272 records from The First Comprehensive Description of the Biodiversity and Biogeography of Antarctic and Sub-Antarctic Intertidal Communities. 12 records from (Table III) Abundance of crustacea orders during RSS James Clark Ross cruise JR144. 2 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2007. 36 records from Early succession in benthic hard bottom communities in Kongsfjorden, Svalbard - abundance. 5 records from Patrick Roper’s Notebooks. 103 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 4 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 1 records from Issumer Fleuth. 20319 records from National Benthic Inventory. 1 records from A new species of the genus Rhinoecetes Just, 1983 (Crustacea: Amphipoda: Ischyroceridae) from Japan. 12 records from OEH Atlas of NSW Wildlife. 41 records from Marine Non Native Species records from Natural Resources Wales (NRW) Monitoring Research and Ad-hoc Sightings. 4 records from A new genus and species of freshwater Hadziidae, Fluviadulzura spinicauda gen. nov., sp. nov. from rivers in Victoria, Australia (Amphipoda). 2 records from Dorotea gen. nov., a new bathyal genus (Amphipoda, Eusiridae) from the Solomon Sea (Papua New Guinea). 4 records from Abundance of benthos infauna at station GIK23013-2. 1 records from Tag der Artenvielfalt mit SchülerInnen des Europa-Gymnasiums in Wörth am Rhein. 3 records from A new groundwater species of Pseudoniphargus (Amphipoda: Pseudoniphargidae) fromAlgeria. 1 records from Lustadter Wald .. 4 records from KNWR Entomology Collection. 3 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 199 records from CSIRO, Cruise SS200507, Benthic Biodiversity, Western Australia, 2005. 8 records from AquaInvaders. 1 records from Klutensee. 44 records from Seasearch Marine Surveys in the Isle of Man. 1 records from DSMZ Bacteria. 253 records from Terrestrial and liminic invertebrates systematic collection NTNU University Museum. 1 records from CAS Entomology (ENT). 49 records from A review of the families and genera of the superfamily PLATYSCELOIDEA Bowman & Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea), together with keys to the families, genera and species. 3 records from Carnet B Lorraine. 1123 records from Seasearch Marine Surveys in England. 10 records from BioChem: Zooplankton of St. Margarets Bay 1968 to 1971.. 1 records from Palaeontologische Sammlung der Freien Universitaet Berlin. 6 records from Two new species of sand-burrowing amphipods of the genus Haustorius Müller, 1775 (Amphipoda: Haustoriidae) from the northwestern Gulf of Mexico. 22 records from Metagenomic community analysis of marine zooplankton using two plankton nets. 1115 records from Australian River Assessment System. 1 records from Tag der Artenvielfalt am Bruckenwasen. 18 records from AEV données faune. 4 records from Inventaire de l'îlot du Lédénez Vraz. 5328 records from Freshwater samples in MZNA-INV-FRW: Macroinvertebrate samples from the water quality monitoring network along the Ebro Basin. 5 records from Elasmopus sivaprakasami sp. nov., a new species of amphipod (Senticaudata, Maeridae) from Gujarat State, India. 5 records from Evaluation of filtration and DNA extraction methods for environmental DNA biodiversity assessments across multiple trophic levels.. 10 records from Auburn University Museum of Natural History Mollusks. 244 records from NSW Waterwatch. 168 records from RMT Trawl catch from the 1992/93 V6 KROCK voyage. 1 records from Altholzparzelle Eilenriede Hannover. 2 records from Sbp-BioBlitz2017_60years-BiodiversityData. 676 records from COMARGIS: Information System on Continental Margin Ecosystems. 253 records from National Trust Species Records. 1715 records from Centre for Biodiversity Genomics - Canadian Specimens. 1 records from BUND Naturschutzzentrum St. Julian. 2 records from New species of Victoriopisa Karaman & Barnard, 1979 (Crustacea: Amphipoda: Eriopisidae) from Vembanad backwaters, Southwest coast of India. 11768 records from RBINS DaRWIN. 8 records from Fife Nature Records Centre combined dataset. 2 records from Données naturalistes de Jean-Michel LEMAIRE. 4168 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 86 records from SER Species-based Surveys. 9 records from Fauna inventories from the intertidal zone in Wimereux, France. 33 records from Analysis of the genus Sunamphitoe Spence Bate, 1857 (Amphipoda: Ampithoidae) with descriptions of eight new species. 617 records from Queen Victoria Museum Art Gallery provider for OZCAM. 558 records from River Macrophytes Database. 107 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 31 records from Programme Ecoscope: données d'observations des écosystèmes marins exploités. 1 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 1 records from LBV-Kindergruppen Markt Tussenhausen. 1 records from Amplicon-Based Illumina Sequencing Reveals High Diversity of Phytoplankton in the Coastal Waters of Qinhuangdao. 3 records from Fauna y flora del municipio de Paipa, Boyacá. 1241 records from Nahant Collection. 1 records from Opisa takafuminakanoi, a new species of Opisidae from Hokkaido, Japan (Crustacea: Amphipoda). 88 records from SOMBASE. 312 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE293. 2 records from Inventaires PnrL "Mares". 6 records from Ontario BioBlitz Species Records. 16 records from SIRFF - FNE Centre-Val de Loire - Données 2015. 8 records from The Australian Zooplankton Database (1938 onwards). 1 records from Collection Bernstein - SMF. 1 records from Bayerische Donau - Tapfheim. 2 records from Harold W. Manter Laboratory of Parasitology Collection. 1 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 2 records from A new species of Stephonyx (Amphipoda, Amphilochida, Lysianassoidea) from Brazil. 219 records from Waarnemingen.be - Non-native animal occurrences in Flanders and the Brussels Capital Region, Belgium. 16 records from UAM Insect Observations (Arctos). 684 records from Archives of the Arctic Seas Zooplankton. 6 records from Abundance of benthos infauna at station GIK23040-1. 2 records from Königstetten. 25 records from Shropshire Ecological Data Network database. 2 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 181 records from Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 250 records from Invasive Non-Native Species. 7 records from Pelagic Microbiome: viruses to protists. 16S and 18S data from oceanic samples collected at the chlorophyll maximum.. 1 records from Benthic meiofauna abundance in surface sediment during cruise CD86. 40 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1 records from Fluss - Vielfalt. 1233 records from NaGISA Project. 2236 records from UF Invertebrate Zoology. 84 records from Invertebrate Common Standards Monitoring and ISIS Test Data. 2 records from Two new species of Ampithoidae (Crustacea: Amphipoda) from northeastern Brazil. 2 records from Parc_National_du_Mercantour_2017_12_18. 6 records from General Biodiversity Records from Ireland. 57 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 3 records from A new species and new record of the genus Sinocorophium (Crustacea, Amphipoda, Corophiidae) from Korean Waters. 3 records from Validation of the replacement name Eusceliotes Stebbing, 1888 for the pelagic hyperiidean amphipod genus Euscelus Claus, 1879 (Crustacea: Amphipoda: Hyperiidea: Parascelidae), preoccupied by Euscelus Schoenherr, 1833 (Insecta: Coleoptera: Attelabidae). 5 records from A new species of Microdeutopus, M. periergos sp. nov. (Crustacea, Amphipoda, Senticaudata, Aoridae) from Cyprus (East Mediterranean Sea). 13 records from (Table 2a) Abundance of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 4 records from Ecological surveys from Bardon Hill undertaken in the period 2000 to 2007. 2 records from Abundance of benthos infauna at station GIK23046-1. 133 records from Schellenberg A. 1936. The fishery grounds near Alexandria. Amphipoda Benthonica. Notes and memoirs No 18.. 343 records from Seasearch Marine Surveys in Scotland. 1 records from Langes Tannen in Uetersen. 2 records from 3. Tag der Artenvielfalt Hockenheim. 296 records from Benthic communities and environmental parameters in three Mediterranean ports (Sardinia, Crete, Tunisia). 309 records from Scottish river macro-invertebrate records from 2007 collected by SEPA. 2 records from Données naturalistes de Benoit LECAPLAIN. 512 records from Zooplankton in the bay of Biscay (1995-2004 Yearly spring DEPM surveys). 58 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 1 records from DNA metabarcoding assays reveal a diverse prey assemblage for Mobula rays in the Bohol Sea, Philippines. 4 records from Colorado Plateau Museum of Arthropod Biodiversity. 79 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 68 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 1 records from Wangerooge. 78 records from marine sediment metagenome Metagenome. 13 records from RMT Trawl catch from the 2005/06 V3 BROKE-West voyage - Zooplankton. 9 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 3 records from Clare Biological Records Centre Dataset 2004-2007. 1 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 5 records from Abundance of benthos infauna at station POS128/2_267. 2 records from David Dodds Associates Ltd - Species Records. 1 records from Biosphäre Bliesgau. 15 records from National Trust for Scotland Species Records. 450 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 1 records from Wanderweg am Windebyer Noor (bei Eckernförde). 17 records from Two new species of the genus Crangonyx Bate, 1859 (Amphipoda: Crangonyctidae) from the St. Marks River Basin with notes on the “ Crangonyx floridanus complex ”. 10 records from Amphipoda (Crustacea) from Palau, Micronesia: Families Maeridae and Melitidae. 1158 records from Base de datos y colección de anfípodos (Hyperiidea:Crustacea) de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 17 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 4 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 76 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 62 records from Soft sediment assemblages at Casey Station: Brown Bay Grid - samples taken along a pollution gradient.. 4 records from Limnic freshwater pelagic invertebrates biogeographical mapping/inventory NTNU University Museum. 1 records from Bach. 88 records from Structure and function of contemporary food webs on Arctic shelves: A panarctic comparison. The pelagic system of the Kara Sea- communities and components of carbon flow. 451 records from Ocean Genome Legacy Collection. 36 records from Natural History Museum Rotterdam (NL) - Invertebrata miscellaneous Collection. 379 records from AAD Benthic Sampling Database. 100 records from IPOE_Benthos_Steffens. 1 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 2 records from Meiofauna abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 15 records from Stable Isotope Compositions of tubeworms, mussels, and their associated fauna in Gulf of Mexico hydrocarbon seeps. 5 records from North Merseyside Local Species Data (DEFRA Grant 23169). 8 records from AKG-Gelände in Bensheim. 6 records from Walldorf-Wiesloch: "Natur über den Gleisen". 1 records from FFH-Gebiet Ahrbachtal. 427 records from National Invasive Species Database. 32 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 15 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 1 records from MfN - Fossil invertebrates Ia. 11 records from Marine sediment metagenome raw sequence reads. 3 records from Marine metagenome ICM_GPS. 1 records from CSIRO, Cruise SS200001, Marine Biodiversity, South and Southeast Australia, 2001. 53 records from Bob Merritt dataset of Nottinghamshire invertebrates. 57 records from New species and phylogeny of landhoppers in the genus Waematau Duncan, 1994 (Crustacea: Amphipoda: Talitridae) from northern New Zealand. 4007 records from National indicator data for river condition in New Zealand. 2 records from HBRG Highland Seashore Project Dataset. 402 records from 1778-1998 Ivor Rees North Wales Marine Fauna Ad-hoc sightings shore and ship-based surveys. 171 records from Plymouth sound dataset. Soft sediment macrobenthos from the Plymouth Sound from 1995. 1 records from NEW-2. 524 records from Occurrences in SinBIOTA. 169 records from Computarización de la Colección Nacional de Crustáceos del Instituto de Biología, UNAM y elaboración de su catálogo. 1 records from Kohlbach (Sulzfeld). 199 records from Victorian Biodiversity Atlas. 5 records from Museum of Southwestern Biology, Division of Arthropods. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences